2021
DOI: 10.1111/puar.13415
|View full text |Cite
|
Sign up to set email alerts
|

Exposing the Unfinished Business of Building Public Administration in Late Democracies: Lessons from the COVID‐19 Response in Brazil

Abstract: The COVID‐19 pandemic has exposed fundamental flaws in the design of public administration in late democracies. While much writing to date focuses on the initial and vital responses to COVID‐19, the magnitude of this event also furthers insights into the risks of incomplete institutional designs and practices, such as the case of Brazil, an example of the administrative flaws in late democracies. This article is not a critique of responses to COVID‐19 per se, but an examination of these considering democratiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…We applied t-tests to compare the mean of the financial support municipalities received between these groups (Table 4). Such an effect was verified in the municipalities with less than 50,000 inhabitants (Panel C), representing 88% of the municipalities with the same autonomy and responsibilities for providing health, education, and urban infrastructure as the biggest cities (Oliveira & Berman, 2021).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…We applied t-tests to compare the mean of the financial support municipalities received between these groups (Table 4). Such an effect was verified in the municipalities with less than 50,000 inhabitants (Panel C), representing 88% of the municipalities with the same autonomy and responsibilities for providing health, education, and urban infrastructure as the biggest cities (Oliveira & Berman, 2021).…”
Section: Resultsmentioning
confidence: 77%
“…We applied t ‐tests to compare the mean of the financial support municipalities received between these groups (Table 4). Such an effect was verified in the municipalities with less than 50,000 inhabitants (Panel C), representing 88% of the municipalities with the same autonomy and responsibilities for providing health, education, and urban infrastructure as the biggest cities (Oliveira & Berman, 2021). Moreover, municipalities' size, degree of financial dependency on central government transfers, and capacity to collect their revenues are already known proxies for vulnerabilities (Padovani et al., 2021).…”
Section: Resultsmentioning
confidence: 82%
“…However, poor coordination between federal, state, and municipal authorities led to inconsistencies between narratives and practices at various levels of government and resulted in confusion (Da Fonseca, Nattrass, Arantes & Bastos, 2021 ). There was also unclear and weak leadership (Puppim de Oliveira & Berman, 2021 ), illustrated by the replacement of four ministers of health. Ambiguous leadership and the Supreme Court intervention cast doubt on the capacity of the executive branch to coordinate the implementation of a social isolation policy and act as a legitimate locus of control over the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As research on policymaking has indicated many times, a division of authority between levels of government and fragmentation in the locus of governance commonly creates ambiguity in accountability and responsibility (Kobrin, 2009 ; Puppim De Oliveira & Berman, 2021 ). The misalignment in Brazil encouraged a further politicization of issues, such as on the pros and cons of medical treatments that should have been the responsibility of health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, governments, rich or poor, should want to embrace good governance for strategic purposes as well as for the overall development of their countries. This perceived strength of good governance improves state capacity to deal with mega crises such as the COVID‐19 pandemic (de Oliveira & Berman, 2021 ). Peters et al.…”
Section: Vaccine Equity and Good Governance: Theoretical Insights And...mentioning
confidence: 99%